Advances and Potentials of Polydopamine Nanosystem in Photothermal-Based Antibacterial Infection Therapies - Fan, Shuhao; Lin, Wensen; Huang, Yifan; Xia, Jiaojiao; Xu, Jun-Fa; Zhang, Junai; Pi, Jiang (Frontiers in Pharmacology, 2022)
Bacterial infection remains one of the most dangerous threats to human health due to the increasing cases of bacterial resistance, which is caused by the extensive use of current antibiotics. Photothermal therapy (PTT) is similar to photodynamic therapy (PDT), but PTT can generate heat energy under the excitation of light of specific wavelength, resulting in overheating and damage to target cells or sites. Polydopamine (PDA) has been proved to show plenty of advantages, such as simple preparation, good photothermal conversion effects, high biocompatibility, and easy functionalization and adhesion. Taking these advantages, dopamine is widely used to synthesize the PDA nanosystem with excellent photothermal effects, good biocompatibility, and high drug loading ability, which therefore play more and more important roles for anticancer and antibacterial treatment. PDA nanosystem-mediated PTT has been reported to induce significant tumor inhibition, as well as bacterial killings due to PTT-induced hyperthermia. Moreover, combined with other cancer or bacterial inhibition strategies, PDA nanosystem-mediated PTT can achieve more effective tumor and bacterial inhibitions. In this review, we summarized the progress of preparation methods for the PDA nanosystem, followed by advances of their biological functions and mechanisms for PTT uses, especially in the field of antibacterial treatments. We also provided advances on how to combine PDA nanosystem-mediated PTT with other antibacterial methods for synergistic bacterial killings. Moreover, we further provide some prospects of PDA nanosystem-mediated PTT against intracellular bacteria, which might be helpful to facilitate their future research progress for antibacterial therapy.